1998
DOI: 10.1136/ip.4.3.176
|View full text |Cite
|
Sign up to set email alerts
|

Harstad injury prevention study: prevention of burns in young children by community based intervention

Abstract: Objective-To describe the long term eVectiveness of a community based program targeting prevention of burns in young children. Design-Quasiexperimental. Setting-The Norwegian city of Harstad (main intervention), six surrounding municipalities (intervention diVusion), and Trondheim (reference). Participants-Children under age 5 years in the three study populations. Methods-Outpatient and inpatient hospital data were coded according to the Nordic system, and collected as part of a national injury surveillance sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
11

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 10 publications
1
48
0
11
Order By: Relevance
“…12 In comparison, the "Harstad Injury Prevention Study"-a community based educational campaign in Norway-showed long term declines in scald and burn injury rates in children under 5 years in the intervention community, compared with an increase in injury rates in the control community. 13 …”
Section: Discussionmentioning
confidence: 99%
“…12 In comparison, the "Harstad Injury Prevention Study"-a community based educational campaign in Norway-showed long term declines in scald and burn injury rates in children under 5 years in the intervention community, compared with an increase in injury rates in the control community. 13 …”
Section: Discussionmentioning
confidence: 99%
“…7,8 There was an increasing trend in scalds from electric kettles, devices which were unknown in the 1980s. In 1993, no case was recorded, but in 2000, there were 22 cases.…”
Section: Burn Hazardsmentioning
confidence: 99%
“…Den skadeforebyggende modellen fra Harstad har vist seg effektiv i et mindre lokalsamfunn. Den omfatter både aktive og passive forebyggende tiltak via en kommunal handlingsplan der helsesøstertjenesten spiller en spesielt aktiv rolle (7). Det hadde vaert interessant å se om liknende, lokale intervensjoner av høy kvalitet, kunne ført til en reduksjon i antall brannskader blant barn i Bergen i løpet av den neste niårsperioden.…”
Section: Diskusjonunclassified
“…De fleste brannskader er forutsigbare og kan forebygges med enkle midler. Forebyggende intervensjoner kan effektivt hindre brannskader, noe som er vist i både utenlandske og norske studier (7,8). En Cochrane-oversikt fra 2004 etterlyser flere gode studier av effekten av kommunalt baserte, brannskadeforebyggende tiltak (8).…”
unclassified